2011
DOI: 10.1038/nm.2411
|View full text |Cite
|
Sign up to set email alerts
|

Circulating urokinase receptor as a cause of focal segmental glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) is a cause of proteinuric kidney disease, compromising both native and transplanted kidneys. Treatment is limited because of a complex pathogenesis, including unknown serum factors. Here we report that serum soluble urokinase receptor (suPAR) is elevated in two-thirds of subjects with primary FSGS, but not in people with other glomerular diseases. We further find that a higher concentration of suPAR before transplantation underlies an increased risk for recurrence of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
869
8
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 750 publications
(915 citation statements)
references
References 45 publications
23
869
8
5
Order By: Relevance
“…Wei et al [37] found that suPAR is elevated in nearly two-thirds of patients with primary FSGS and that a higher pre-transplant level correlates with increased risk of recurrence. suPAR-mediated activation of β3 integrin is the putative mechanism of action of this molecule.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al [37] found that suPAR is elevated in nearly two-thirds of patients with primary FSGS and that a higher pre-transplant level correlates with increased risk of recurrence. suPAR-mediated activation of β3 integrin is the putative mechanism of action of this molecule.…”
Section: Pathogenesismentioning
confidence: 99%
“…High suPAR levels in the circulation were linked to recurrent FSGS post-transplantation [37]. Podocyte foot process effacement, the initial histological sign of recurrent FSGS, correlates with circulating suPAR levels at the time of diagnosis [42].…”
Section: Pathogenesismentioning
confidence: 99%
“…While children typically respond well to steroids and are often treated empirically without a kidney biopsy, those who are steroid-dependent, steroid-resistant and/or frequent relapsers, pose a therapeutic challenge. While the underlying pathophysiology is still being actively investigated, T-cell dysfunction and various permeability factors have been implicated in the pathogenesis [78], [79] and [80]. RTX has been used with some success in children with steroid-dependent idiopathic nephrotic syndrome, as shown in several case reports [81], [82], [83] and [84].…”
Section: Focal Segmental Glomerulosclerosis and Minimal Change Diseasementioning
confidence: 99%
“…FSGS commonly recurs after transplantation. Wei et al [7] also found that high concentrations of suPAR before transplantation were associated with increased risk for recurrence of FSGS after transplantation. They next used three mouse models to explore the effects of suPAR on kidney function and morphology.…”
mentioning
confidence: 94%
“…Wei et al [7] then introduced the next startling findings regarding uPAR in podocytes. They reported that suPAR, introduced above, is elevated in about two thirds of patients with FSGS, but not in patients with other glomerular diseases.…”
mentioning
confidence: 99%